The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/aem.00869-17
|View full text |Cite
|
Sign up to set email alerts
|

Raffinose Induces Biofilm Formation by Streptococcus mutans in Low Concentrations of Sucrose by Increasing Production of Extracellular DNA and Fructan

Abstract: Streptococcus mutans is the primary etiological agent of dental caries and causes tooth decay by forming a firmly attached biofilm on tooth surfaces. Biofilm formation is induced by the presence of sucrose, which is a substrate for the synthesis of extracellular polysaccharides but not in the presence of oligosaccharides. Nonetheless, in this study, we found that raffinose, which is an oligosaccharide with an intestinal regulatory function and antiallergic effect, induced biofilm formation by S. mutans in a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 56 publications
1
25
1
2
Order By: Relevance
“…Interestingly, exogenous raffinose has recently been shown to promote biofilm formation by Streptococcus mutans by promoting aggregation of extracellular DNA into the biofilm matrix. Biofilm formation was unaffected by deletion of the α-galactosidase gene agaL , indicating that the effect was unrelated to metabolism of any internalized raffinose (22). Thus, it is conceivable that the reduced capacity of S.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, exogenous raffinose has recently been shown to promote biofilm formation by Streptococcus mutans by promoting aggregation of extracellular DNA into the biofilm matrix. Biofilm formation was unaffected by deletion of the α-galactosidase gene agaL , indicating that the effect was unrelated to metabolism of any internalized raffinose (22). Thus, it is conceivable that the reduced capacity of S.…”
Section: Discussionmentioning
confidence: 99%
“…So far, what has been described in the literature in relation to ROF components raffinose-induced biofilm formation by S . mutans in a mixed culture with sucrose [ 27 ]. Further, it has been reported that contribute to the extracellular polysaccharides production in some oral bacteria [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inulin is known to be an important part of the biofilm produced by oral Streptococcus mutans , and inulin accumulating in dental plaques is hydrolysed when environmental carbon sources are scarce, which in turn may cause dental carries in the long run (Krzyściak, Jurczak, Kościelniak, Bystrowska, & Skalniak, ). Nagasawa, Sato, and Senpuku () studied the effects of sucrose and raffinose, a trisaccharide composed of ᴅ‐galactose, ᴅ‐glucose, and ᴅ‐fructose, on biofilm formation of S. mutans, and found that at sucrose concentrations insufficient to induce biofilm formation, raffinose contributed to biofilm structure by increasing aggregation of eDNA while also being a substrate for raffinose‐based inulin production. Because the ᴅ‐glucose moiety in raffinose is located between the other two monosaccharides, glucosyltransferase enzymes cannot use raffinose as donor substrate to synthesize glucans.…”
Section: Microbial Fructansmentioning
confidence: 99%